Nurses' Stress and Anxiety in Acute and Intermediete Ward at Mental Health Hospital Riau - Nelvica Salny; Eka Malfasari (Talenta Publisher, 2019)
Psychiatric health nurses work with patients who experience ineffective coping mechanisms for the illness they are experiencing. This makes psychiatric nurses often deal with patients who show different types of symptoms with behavioural problems such as violence, assault, and suicide when hospitalized for anxiety and stress for nurses. The purpose of this study was to determine the difference of anxiety level and stress on nurses in acute room and intermediate room. The type of this study was quantitative with comparative analytic design using cross sectional study approach. The sample in this study were 19 acute room nurses and 90 intermediate room nurses. This research was conducted in April 2018 in the treatment room at RSJ Riau Province. The measuring tool used the DASS 42 questionnaire using anxiety and stress questionnaires. The analysis used univariate and bivariate analysis using independent t test statistic for stress variable and Mann Whitney Test for anxiety variable. The results of this study showed there was no difference in the level of anxiety on the nurses in the acute room and intermediate room seen from p value of 0.952 (> 0.05). And there is a difference of stress level on nurses in acute room and intermediate room seen from p value 0,000 (<0,005). Based on the results of this study, nurses are expected to recognize the response level of anxiety and stress experienced by nurses.